(untitled) (Journal of Hama University, 2020)
Idiomatic expressions raise many challenges for translators. The importance of idioms, generally in language and particularly in translation, as well as the way(s) in which they are translated, is investigated in this paper. Within the process of translation, idiomatic expressions are subject to different approaches opted for by translators when they transfer them from the source text into the target text. The present paper is a brief descriptive qualitative study of the translation of idiomatic expressions in literary texts from Arabic into English. The study is an attempt to investigate how translators deal with idioms when transferring them to the target language, and to determine whether the target text fulfills the lexical and pragmatic characteristics of the idiomatic expression or not. The subject of the analysis is a novel, Sabriya: Damascus Bitter Sweet, by the Syrian author Ulfat Idilbi translated by Peter Clark. Two questions are investigated: How does the translator deal with these idiomatic expressions when translating them into English? And how can we achieve acceptable equivalents of idiomatic expressions in the novel under study? To achieve these objectives, the study relies on the principles of the approach proposed by Baker (1992) which are reflected at a number of levels within the text, from the word up through the components of texts to the worldviews that underlie cultures and languages.